Self-confidence and its relation to the apparent behavior of women participating in sports halls (Journal of the College of Basic Education, 2022)
Self-confidence is one of the most important elements of the personality of the individual and the apparent behavior is like the woman of their personality and the extent of their relationship to the society and accept them and that there is a relationship between self-confidence and some aspects of personality and behavior, the behavior is one of the most important elements of the personality that depends on the extent of self-confidence itself which is affected by environmental conditions and nature The field and the weakness of self-confidence greatly affects the behavior of the virtual individual and his treatment and its relationship with the community so many problems and obstacles. Here is the importance of research in identifying the relationship between phenotypic behavior and self-confidence among women participating in sports halls. The problem of research is that it is difficult to show the proper appearance behavior of women participating in sports halls. This is due to the weakness of their self-confidence resulting from increasing their weight and the society's perception of them or other causes. The objectives of the research are to identify the level of self-confidence and the level of apparent behavior and to identify the relationship between self-confidence and the apparent behavior of women participating in sports halls. The hypothesis of research was that there was a statistically significant relationship between self-confidence and apparent behavior among women participating in sports halls. The second part of the researcher discusses the concept of self-confidence and the symptoms of weak self-confidence and the concept of descriptive behavior and theories. The third section discusses the type of curriculum used in the research of the survey method and the same research of women participating in the gymnasium number (20). The fourth chapter deals with the presentation, analysis and discussion of the results. And then the fifth section of the conclusions and recommendations, it was found that there is an inverse relationship between self-confidence and behavior and the appearance of the same research with a low level of phenotypic behavior. The most important recommendations are to encourage women to exercise continuously because they contribute to the ideal weight and beautiful appearance and promote the confidence of individuals themselves .